EXPERIMENTAL RESULTS ON THE EFFECTIVENESS OF AN IMPROVED EXCAVATOR BUCKET TOOTH DESIGN (Web of Technology: Multidimensional Research Journal, 2024)
In the process of drilling, in case of untimely lifting of cuttings from the bottom of the well, i.e. when the particles of the destroyed cuttings linger on the surface of the bottom of the well and under the action of hydrostatic pressure, a decrease in the efficiency of the rock cutting tool is observed. This article discusses the movement of broken cuttings at the bottom of the well, its impact on the efficiency of the drilling process, and presents the results of experimental work to prevent the cuttings regime at the bottom of the well based on the improvement of the design of the rock cutting tool.